Cyber Notary Problems in Legal Reform in Indonesia - Sujiati, Ani Eva; Ifana, Visca Aliya; Ahimsya, Moh Galih Raka Siwi; Listyawati, Peni Rinda (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2024)
Cyber notary is a concept of using digital technology that is expected to bring great benefits to the legal system and society in Indonesia. Along with the development of digital technology, this concept is proposed as a solution to improve efficiency and security in notary services. Cyber notary allows the process of document validation and electronic signing to be carried out online, utilizing technologies such as blockchain and digital signatures. However, its implementation still faces various challenges. One of the main problems is the lack of comprehensive and specific regulations governing the use of digital technology in notary practice. In addition, concerns about the security and privacy of electronic data are serious obstacles. Cyber attacks and the risk of forgery of electronic documents require a stronger and more sophisticated security mechanism. In addition, in remote areas that still experience limited internet access. The lack of understanding and technical expertise among notaries who are tech-savvy also hinders the adoption of cyber notary. These factors emphasize the need for increased capacity and training for notaries to adapt digital technology in cyber notary practice. This study uses normative legal research with a legislative approach(statute approach) that examines regulations and laws relating to legal issues regarding cyber notary. This study examines the implementation and challenges faced in implementing the concept of